2023
DOI: 10.3390/antiox12081606
|View full text |Cite
|
Sign up to set email alerts
|

Rhythm and ROS: Hepatic Chronotherapeutic Features of Grape Seed Proanthocyanidin Extract Treatment in Cafeteria Diet-Fed Rats

Abstract: Polyphenols play a key role in the modulation of circadian rhythms, while the cafeteria diet (CAF) is able to perturb the hepatic biological rhythm and induce important ROS production. Consequently, we aimed to elucidate whether grape seed proanthocyanidin extract (GSPE) administration recovers the CAF-induced hepatic antioxidant (AOX) misalignment and characterize the chronotherapeutic properties of GSPE. For this purpose, Fischer 344 rats were fed a standard diet (STD) or a CAF and concomitantly treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…Several pharmacological interactions involving resveratrol were also discovered and because of the potential for these interactions to reduce the efficacy of the medication, they are considered hazardous [27]. High-dose resveratrol has hormetic effects in vitro (micromolar range in cell culture media) and in vivo (nanomolar range in the blood) [28][29][30], including pro-oxidant effects [29][30][31][32][33][34], but it also has toxic side effects, such as disrupting the thyroid and causing goiter if used for an extended period of time. Thus, it is important to identify the actual biologically effective concentration range at which this compound should be supplemented in human subjects [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Several pharmacological interactions involving resveratrol were also discovered and because of the potential for these interactions to reduce the efficacy of the medication, they are considered hazardous [27]. High-dose resveratrol has hormetic effects in vitro (micromolar range in cell culture media) and in vivo (nanomolar range in the blood) [28][29][30], including pro-oxidant effects [29][30][31][32][33][34], but it also has toxic side effects, such as disrupting the thyroid and causing goiter if used for an extended period of time. Thus, it is important to identify the actual biologically effective concentration range at which this compound should be supplemented in human subjects [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, GSPE was reported to improve the metabolic status after light/dark cycle disruption [40]. More recently, we have also shown that GSPE administration restored the diurnal rhythms of antioxidant enzyme gene expression lost by the CAF in the liver [19].…”
Section: Introductionmentioning
confidence: 60%
“…In line with this, our group recently described the restoration of the diurnal rhythmicity of GPx1, lost by the CAF, through GSPE treatment in a time-of-day dependent manner. This mechanism could explain the increase in the expression of this gene and the enhancement of the antioxidant response [19]. However, the expressions of two main targets of NRF2, including Sod2, the mitochondrial isoform of SOD, and Sesn2, which is fundamental against oxidative stress, remained unresponsive to the GSPE treatment, as no differences were found regardless of the photoperiod condition.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation